Tumor-derived osteopontin isoforms cooperate with TRP53 and CCL2 to promote lung metastasis - Giopanou, I; Lilis, I; Papaleonidopoulos, V; Agalioti, T; Kanellakis, NI; Spiropoulou, N; Spella, M; Stathopoulos, GT (Taylor and Francis, 2016)
The lungs are ubiquitous receptacles of metastases originating from various bodily tumors. Although osteopontin (SPP1) has been associated with tumor dissemination, the role of its isoforms in lung-directed metastasis is incompletely understood. We employed syngeneic mouse models of spontaneous and induced lung-targeted metastasis in C57BL/6 mice competent and deficient in both Spp1 alleles. Tumorderived osteopontin expression was modulated using either stable anti-Spp1 RNA interference, or forced overexpression of intracellular and secreted Spp1 isoforms. Identified osteopontin’s downstream partners were validated using lung adenocarcinoma cells conditionally lacking the Trp53 gene and Ccr2-deficient mice. We determined that host-derived osteopontin was dispensable for pulmonary colonization by different tumor types. Oppositely, tumor-originated intracellular osteopontin promoted tumor cell survival by preventing tumor-related protein 53-mediated apoptosis, while the secretory osteopontin functioned in a paracrine mode to accelerate lung metastasis by enhancing tumor-derived C–C-motif chemokine ligand 2 signaling to cognate host receptors. As new ways to target osteopontin signaling are becoming available, the cytokine may constitute an important therapeutic target against pulmonary involvement by cancers of other organs.